2002
DOI: 10.1136/oem.59.8.562
|View full text |Cite
|
Sign up to set email alerts
|

Work related symptoms among sewage workers: a nationwide survey in Sweden

Abstract: Aims: To assess the risk for work related symptoms among sewage workers in Sweden using a postal questionnaire. Methods: All municipalities in Sweden were contacted and asked to provide addresses of sewage workers and controls. Controls were recruited among other municipal workers not exposed to sewage, such as workers in drinking water plants and gardeners. A questionnaire was sent to the subjects and after two reminders, the response rate was 74% among sewage workers and 59% among controls. Results: Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 27 publications
5
57
0
Order By: Relevance
“…In the current study, investigating the frequency of some of central nervous system symptoms that may suggest cognitive impairment ( memory defects, and lack of concentration), revealed statistically significant higher percentage of these symptoms among the exposed group compared to the controls ( table 1, P<0.01). These results are greatly supported by a similar study of Thorn et al, (2002) who reported significantly increased risks for similar symptoms among sweden sewage workers. Also similar symptoms were reported among ex-workers and neighboring residents who were exposed to hydrogen sulfide and other reduced-sulfur compounds emitted from an oil refinery in concentrations ranged from a low of 10 ppb to 8.…”
Section: Discussionsupporting
confidence: 80%
“…In the current study, investigating the frequency of some of central nervous system symptoms that may suggest cognitive impairment ( memory defects, and lack of concentration), revealed statistically significant higher percentage of these symptoms among the exposed group compared to the controls ( table 1, P<0.01). These results are greatly supported by a similar study of Thorn et al, (2002) who reported significantly increased risks for similar symptoms among sweden sewage workers. Also similar symptoms were reported among ex-workers and neighboring residents who were exposed to hydrogen sulfide and other reduced-sulfur compounds emitted from an oil refinery in concentrations ranged from a low of 10 ppb to 8.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, Rylander 14 reported an increased risk of joint pain among sewage workers. Thorn et al 26 attributed this increased risk of joint pain to an inflammatory/systemic response among sewage workers. Possible causative agents have been reported as viruses such as Norwalk virus, other microorganisms, and endotoxins.…”
Section: Commentmentioning
confidence: 99%
“…A variety of infectious agents have been postulated as important in the etiology of multiple sclerosis, but a causal association has not been demonstrated convincingly for any infectious agent. [26][27][28][29] An increased risk for multiple sclerosis is likely to involve a combination of genetic susceptibility and environmental exposures. 30 In addition, a clustering of multiple sclerosis in Galion, OH, from 1982 to 1985 was attributed to an excess concentration of heavymetal wastes, especially cadmium and chromium, in sewage and river water.…”
Section: Commentmentioning
confidence: 99%
“…Previous researches reported that musculoskeletal disorders (periarthritis of shoulder, cervical spondylopathy, arthritis, and so on) 6,9 and respiratory symptoms (chronic bronchitis) 4,[10][11][12] were common diseases in sanitation workers. In the survey carried out by Liang et al, they performed a comparison of the respiratory function between sanitation workers and teachers, the results showed that the respiratory function of sanitation workers significantly decreased after ten years' work, which was related to the service time 13 .…”
Section: Discussionmentioning
confidence: 99%